2015
DOI: 10.1089/cap.2014.0128
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Preliminary Study of Aripiprazole for Treatment-Resistant Childhood Obsessive-Compulsive Disorder

Abstract: This very small study of aripiprazole, given to children with OCD resistant to at least 12 weeks treatment with at least two SSRIs and CBT, demonstrated striking improvement in CGI scores (all subsets, p≤0.002) for 13 of 16 children, and halved all CY-BOCS subscores after ∼12 weeks of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Our results may prompt consideration of further research into low-dose D 2/3 agonist treatment for OCD, although, here, considerable caution, rigorous risk assessment, and very careful experimental design are advised given prior reports that pramipexole may cause or worsen compulsive behaviors in some people (Kolla et al 2010). Our data are consistent with the potential therapeutic actions of partial D 2/3 agonists; one such drug, aripiprazole, has already been shown to be effective in augmentation in OCD, with some evidence of efficacy at very low doses (Ercan et al 2015; Janardhan Reddy et al 2017; Muscatello et al 2011; Sayyah et al 2012; Veale et al 2014). Additional mechanistic and pragmatic research is warranted to determine which OCD patients are most likely to benefit from dopaminergic treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Our results may prompt consideration of further research into low-dose D 2/3 agonist treatment for OCD, although, here, considerable caution, rigorous risk assessment, and very careful experimental design are advised given prior reports that pramipexole may cause or worsen compulsive behaviors in some people (Kolla et al 2010). Our data are consistent with the potential therapeutic actions of partial D 2/3 agonists; one such drug, aripiprazole, has already been shown to be effective in augmentation in OCD, with some evidence of efficacy at very low doses (Ercan et al 2015; Janardhan Reddy et al 2017; Muscatello et al 2011; Sayyah et al 2012; Veale et al 2014). Additional mechanistic and pragmatic research is warranted to determine which OCD patients are most likely to benefit from dopaminergic treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, 14 studies that are less methodologically sound are also reported in Table 3: open-label studies with or without randomization (Findling et al 2008b(Findling et al , 2009(Findling et al , 2011Marcus et al 2011a;Ercan et al 2012;Ghanizadeh et al 2014;Ghanizadeh 2016;Lamberti et al 2016;Wang et al 2016;Kim et al 2018;Pan et al 2018) and retrospective studies on files (Olfson et al 2012b;Ercan et al 2015;Akyol Ardic et al 2017) in indications corresponding to FDA approval or off-label indications, such as ADHD, disruptive disorder, emotional regulation disorder, conduct disorder, and resistant obsessive-compulsive disorder. For most of these indications, a significant improvement is reported between the beginning and end of treatment, but the absence of a control group and, in particular, a placebo control group makes it very difficult to conclude that aripiprazole is useful for these nonauthorized indications.…”
Section: Efficacy Datamentioning
confidence: 99%
“…At the end of 12 weeks, there was a significant reduction in the children's Y-BOCS score and improvement in the clinical global impressions–improvement (CGI-I) score. [20] A more recent larger open-label study with 48 children and adolescents who had not responded to at least two SSRIs and CBT also reported similar improvement. [21]…”
Section: Second-generation Antipsychoticsmentioning
confidence: 84%